Interplay Between CMGC Kinases Targeting SR Proteins and Viral Replication: Splicing and Beyond - Pastor, Florentin; Shkreta, Lulzim; Chabot, Benoit; Durantel, David; Salvetti, Anna (Frontiers in Microbiology, 2021)
Protein phosphorylation constitutes a major post-translational modification that critically regulates the half-life, intra-cellular distribution, and activity of proteins. Among the large number of kinases that compose the human kinome tree, those targeting RNA-binding proteins, in particular SR proteins, play a major role in the regulation of gene expression by controlling constitutive and alternative splicing. In humans, these kinases belong to the CMGC (CDKs, MAPKs, GSKs, CLKs) group and several studies indicate that they also control viral replication via direct or indirect mechanisms. The aim of this review is to describe known and emerging activities of CMGC kinases that share the common property to phosphorylate SR proteins, as well as their interplay with different families of viruses, in order to advance toward a comprehensive knowledge of their pro- or anti-viral phenotype and better assess possible translational opportunities